Organisational culture that inhibit the lean implementation - Alkhoraif, Abdullah; McLaughlin, Patrick (The International Academic Forum (IAFOR), 2016)
Lack of research regarding the critical factor of organisational culture related to lean implementation and Culture is the key factor to making the changes for lean implementation (Pakdil and Leonard, 2015a). Implementing lean into industrial SMEs faces difficulties, whereas it is more likely to be implemented successfully in larger companies, which then gain the advantages of lean systems(Karim et al., 2011). Moreover, the culture of an organisation plays a vital role, especially for managers facing the challenge to change that culture(Graham-jones and Muhareb, 2015). According to the European Commission (2003) the purpose of this paper SMEs refer to organisations with fewer than 250 employees. The aim is to develop an Organisational Culture to improve Lean Implementation into Manufacturing Organisation SMEs by analyses the organisational culture aspects that enable and inhibit lean implementation, through a literature review. Finally the question will be what are the organisational culture enablers for lean implementation in manufacturing SMEs. Systematic review methodology applied to this research. The main aim of this research is to develop an organisational culture to facilitate lean implementation before adopting the lean system. It has been observed that the appropriate lean culture enhances the pace of the growth and keeps the firm competitive (Pooyan et al, 2014). These inhibiting factors, and indeed those factors that encourage this behaviour can be graphically displayed and tabulated, allowing deeper analysis of each, to find its roots and, where necessary, remove it from the company culture (Hietschold et al, 2014)
Keywords: Organisational Culture; Lean; Small to Medium Sized (SME)